Reconstruction of Chest Wall by Cryopreserved Sternum Allograft After Resection of Sternal Hemangioma: A Case Report - Sadegh Beigee, Farahnaz; Sheikhy, Ali; Sheikhy, Kambiz (Frontiers in Surgery, 2022)
A 5-year-old girl was referred to our department for a mass of sternum that was previously biopsied and diagnosed as hemangioma. Chest X-ray and CT scan confirmed a large sternal mass. We resected the sternum completely and reconstructed a large anterior chest wall defect by a cryopreserved sternal allograft. In the follow-up of the patient, there was no instability of the chest wall and acceptable cosmetic results.